Deformation Control of Shield Tunnels Affected by Staged Foundation Pit Excavation: Analytical Method and Case Study - Gang Wei; Yebo Zhou; Zhe Wang; Qiankan Wang; Chenyang Lu; Guohui Feng (Buildings)
The unloading effect induced by foundation pit excavation leads to soil deformation, which may adversely affect the underlying tunnel. Foundation pit excavation is a three-dimensional (3D) deformation process, whereas most existing methods are based on a two-dimensional (2D) plane assumption. To improve conventional 2D analysis methods, this study considers the influence of the actual construction sequence on tunnel deformation. A 3D analytical method for evaluating tunnel deformation and stress induced by foundation pit excavation is proposed, based on the image source method and the rotational dislocation-coordinated deformation model. The proposed method is validated through comparative analysis with other methods using monitoring data from three engineering cases. Furthermore, the study examines and discusses the impact of excavation sequences on the final longitudinal displacement of the tunnel. The results indicate that the proposed method provides more accurate predictions of tunnel deformation induced by foundation pit excavation in actual projects. Staged and segmented excavation reduces bottom heave of the foundation pit, thereby mitigating its impact on the underlying tunnel. When the segmentation efficiency is positive, increasing the number of excavation blocks contributes to better tunnel deformation control. However, when the segmentation efficiency is negative, an increase in excavation blocks has an insignificant effect on deformation control or leads to excessive construction workload.